LnChrom: a resource of experimentally validated lncRNA–chromatin interactions in human and mouse. (18th May 2018) - Yu, Fulong; Zhang, Guanxiong; Shi, Aiai; Hu, Jing; Li, Feng; Zhang, Xinxin; Zhang, Yan; Huang, Jian; Xiao, Yun; Li, Xia; Cheng, Shujun
Abstract: Long non-coding RNAs (lncRNAs) constitute an important layer of chromatin regulation that contributes to various biological processes and diseases. By interacting with chromatin, many lncRNAs can regulate that state of chromatin by recruiting chromatin-modifying complexes and thus control large-scale gene expression programs. However, the available information on interactions between lncRNAs and chromatin is hidden in a large amount of dispersed literature and has not been extensively collected. We established the LnChrom database, a manually curated resource of experimentally validated lncRNA–chromatin interactions. The current release of LnChrom includes 382 743 interactions in human and mouse. We also manually collected detailed metadata for each interaction pair, including those of chromatin modifying factors, epigenetic marks and disease associations. LnChrom provides a user-friendly interface to facilitate browsing, searching and retrieving of lncRNA–chromatin interaction data. Additionally, a large amount of multi-omics data was integrated into LnChrom to aid in characterizing the effects of lncRNA–chromatin interactions on epigenetic modifications and transcriptional expression. We believe that LnChrom is a timely and valuable resource that can greatly motivate mechanistic research into lncRNAs. Database URL: http://biocc.hrbmu.edu.cn/LnChrom/